Characterization and Potential Analysis of Paper Waste as Raw Material for Refuse Derived Fuel Pellet (RDF) Substitution (WITHDRAW BY AUTHOR) - Rahmalia, Intan; Listyendah Zahra, Nurulbaiti; Dinan Qonitan, Fatimah; Yenis Septiariva, Iva; Mutiara Sari, Mega; Sarwono, Ariyanti; Lim, Jun-Wei; Suryawan, I Wayan Koko (The Journal of Pure and Applied Chemistry Research, 2023)
This paper is withdrawn upon request from the corresponding author.